2009
DOI: 10.1186/1742-6405-6-1
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 transgene expression in rats causes oxidant stress and alveolar epithelial barrier dysfunction

Abstract: BackgroundHIV-infected individuals are at increased risk for acute and chronic airway disease even though there is no evidence that the virus can infect the lung epithelium. Although HIV-related proteins including gp120 and Tat can directly cause oxidant stress and cellular dysfunction, their effects in the lung are unknown. The goal of this study was to determine the effects of HIV-1 transgene expression in rats on alveolar epithelial barrier function. Alveolar epithelial barrier function was assessed by dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
86
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(95 citation statements)
references
References 48 publications
9
86
0
Order By: Relevance
“…This is significant, because ZO-1 is critical for proper insertion of claudins into functional tight junction strands (7). Also, in an HIV transgenic rat model, we found that impaired alveolar barrier function correlated with decreased ZO-1 expression, consistent with an important role for ZO-1 in alveolar epithelial tight junctions (42). However, ZO-1 expression is not the sole determinant of epithelial barrier function, as cells cultured for 2 days on fibronectin formed a high-resistance monolayer, yet had lower ZO-1 content than Day 2 cells on laminin or type I collagen.…”
Section: Discussionsupporting
confidence: 55%
“…This is significant, because ZO-1 is critical for proper insertion of claudins into functional tight junction strands (7). Also, in an HIV transgenic rat model, we found that impaired alveolar barrier function correlated with decreased ZO-1 expression, consistent with an important role for ZO-1 in alveolar epithelial tight junctions (42). However, ZO-1 expression is not the sole determinant of epithelial barrier function, as cells cultured for 2 days on fibronectin formed a high-resistance monolayer, yet had lower ZO-1 content than Day 2 cells on laminin or type I collagen.…”
Section: Discussionsupporting
confidence: 55%
“…Male hemizygous NL4-3Δgag/pol Fischer 344 rats (HIV-1 Tg; Harlan) have been previously described in detail (18,20).…”
Section: Methodsmentioning
confidence: 99%
“…In this study we investigated the impact of HIV-1/AIDS on the skeleton, using HIV-1 transgenic (Tg) rats, an animal model of HIV-1/AIDS involving the global transgenic expression of a HIV-1 gag/pol deleted provirus (18). This model recapitulates many of the immunological and other metabolic complications associated with HIV-1/AIDS in humans, including wasting, skin lesions, cataracts, and pulmonary, immunological, neurological, cardiac, and renal pathologic processes (18)(19)(20). We now add osteoporosis to this list of complications, and validate the HIV-1 Tg rat for the study of the mechanisms underlying bone loss in HIV-1/AIDS.…”
mentioning
confidence: 99%
“…Lung and plasma glutathione levels are lower in HIV-infected smokers than in HIV-infected nonsmokers (42,43). Recent studies demonstrated that, in a rat model, HIV transgene expression resulted in oxidant stress, and alterations in epithelial barrier function via altered expression of tight junction proteins (44). The impact of antiretroviral therapy on oxidative stress is unclear (45,46).…”
Section: Altered Antioxidant-oxidant Balancementioning
confidence: 99%